Role of IL-35 in sublingual allergen immunotherapy. Issue 1 (February 2019) - Layhadi, Janice A.; Eguiluz-Gracia, Ibon; Shamji, Mohamed H.
Abstract : Purpose of review: Sublingual allergen immunotherapy (SLIT), a disease-modifying treatment for allergic rhinitis, can induce long-term clinical benefits which are mediated by immune responses that include generation of regulatory B (Breg) and T (Treg) cells. The newest member of the IL-12 superfamily, IL-35, is an anti-inflammatory cytokine known to be produced by Breg and Treg cells. Limited studies are available on the role of IL-35 on allergic rhinitis and during SLIT. This review summarizes recent findings relevant to the topic of IL-35 and their role in SLIT. Recent findings: Recombinant IL-35 protein can induce the generation of IL-35-producing Breg and Treg cells with immunosuppressive capacity. Levels of IL-35 and IL-35-inducible Treg (iTR 35) cells are dysregulated in allergic rhinitis patients, which can be restored with SLIT. Mechanism of IL-35-mediated tolerance to allergens includes suppressions of T cell proliferation, Th2 cytokine production, and B cell production of IgE antibodies. Summary: Emerging evidence supports a potential role for IL-35 and iTR 35 cells in tolerance maintenance during SLIT. A better understanding for the role of IL-35 and iTR 35 cells could provide new avenues for the development of clinical biomarker to assess efficacy of allergen immunotherapy and novel therapeutic strategies for allergic rhinitis.